A Developed Optimization Method of Tight Reservoir Porosity. (18th July 2017) - Wu, Fenqiang; Xu, Jingling
Abstract : The optimization method to evaluate the tight reservoir porosity is a difficult technique to use due to its complexity and instability. This paper proposes an improved optimization method to calculate the porosity of tight reservoirs. First, we applied the matrix model which modified the multicomponent model to the problem and it improved the results by deducing a mathematical model. Second, we used the Simulated Annealing Algorithm to calculate the incoherence function, and then based on statistical theory, we obtained the most optimal results. Examples show that the method is effective, and despite the lack of the local experience parameters, its application is valuable in order to evaluate the porosity.